2020
DOI: 10.14742/ajet.5689
|View full text |Cite
|
Sign up to set email alerts
|

Not just digital natives: Integrating technologies in professional education contexts

Abstract: In 2001, Prensky characterised a new generation of learners entering higher education as digital natives – naturally digitally literate and inherently proficient users of technology. While many educational technology researchers have long argued for the need to move beyond the digital native assumptions proposed by Prensky and other futurists, a critical review of the literature reveals that this concept remains influential in academia broadly and within professional education specifically. In light of this, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 47 publications
1
29
0
2
Order By: Relevance
“…Digital literacy of students and young physicians, who are often referred to as the generation of digital natives, is discussed ambivalently in the literature. Although some authors postulate that growing up with digital services may lead to differentiated use in a professional context [ 18 ], other publications stress that the implication of the digital native stereotype would leave learners unsupported and technologies used in inappropriate ways, making further research in this area indispensable [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Digital literacy of students and young physicians, who are often referred to as the generation of digital natives, is discussed ambivalently in the literature. Although some authors postulate that growing up with digital services may lead to differentiated use in a professional context [ 18 ], other publications stress that the implication of the digital native stereotype would leave learners unsupported and technologies used in inappropriate ways, making further research in this area indispensable [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Building on Prensky's interpretation of features of digital natives, namely, grow up with technology, comfortable with multi-tasking, reliant on graphics for communication and thrive on instant gratification and rewards, existing studies on digital natives and their technology adoption mostly focused on student cohort (e.g., Bennett and Maton, 2010 ; Teo, 2013 ; Chen et al, 2016 ; Tran et al, 2020 ), with few studies examining adult users' digital nativity. To address this research gap, studies conducted in a higher education context suggested that university teachers also demonstrated features of digital natives (Smith et al, 2020 ; Huang et al, 2021c ), which empirically supported scholars' doubt about defining digital nativity by age. Despite these efforts, it remains unknown whether and to what extent digital nativity is related to university teachers' technology adoption.…”
Section: Introductionmentioning
confidence: 97%
“…Research examining digital preparedness of graduates entering the health sector has identified gaps between students' actual digital skills and competencies and the requirements of digital or e-health practices (Edirippulige et al, 2018;Gray et al, 2014;Kenny et al, 2016;Knight & Drysdale, 2020). Although e-health competencies are represented in international guidelines and accrediting bodies such as the Australian Medical Council, coverage of health information technologies is often vague or generalised, and is isolated from, rather than integrated with, vocational learning programs (Smith et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we examined students' digital skills and competencies to create a baseline for educators to use this information to design targeted classroom activities and ensure these skills and competencies are relevant to health sector requirements (Smith et al, 2020). The importance of digital practices for learning within the university and for professional and career development was also investigated.…”
Section: Introductionmentioning
confidence: 99%